Peran Manajemen Kepemimpinan, Pelatihan Dan Supervisi Terhadap Pedagogical Content Knowledge Di Madrasah - Mutadi Mutadi; Mudofir Mudofir; Muhammad Munadi (ITB AAS INDONESIA Surakarta, 2021)
Pedagogical knowledge in the context of PP No. 74 of 2008 is more equated with the term teacher pedagogic competence. Teacher pedagogic competence is the ability to manage student learning which at least includes understanding of educational insights or foundations, understanding of students, curriculum/syllabus development, learning design, implementation of educational and dialogical learning, utilization of learning technology, evaluation of learning outcomes, and development students to actualize their various potentials. This research was conducted using a correlational quantitative approach. The quantitative approach in research is an approach that emphasizes analysis on numerical data (numbers) that are processed by statistical methods. Basically, the quantitative approach is carried out in inferential research (in the context of testing the hypothesis) and relies on the conclusion of the results on a null probability of rejecting the hypothesis. With quantitative methods will be obtained the significance of the relationship between the variables studied. In general, quantitative research is research on a large sample. The leadership of high-quality madrasah principals with learning outcomes has been widely documented in various research results. A number of recent studies have shown that superior leadership is one of the determining factors in improving teacher performance, both in terms of professional competence and teacher pedagogy.